STRATEGI BAURAN PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN ANEKA PRODUK CEMILAN JAGUNG DAN KACANG-KACANGAN - Muctar Fahrul; Charles Kapioru; Lika Bernadina (Undana Press, 2021)
This study aims to determine the income and marketing mix strategy in the Sima Indah Home Industry. The research method used in this study is the case study method. The research location was specifically determined with the consideration that IRT Sima Indah is one of the production centers for processing corn and beans in Kupang City and processed products from the local industry were marketed to almost all mini markets and supermarkets in Kupang City. The data collected are primary data and secondary data. The data collected is then analyzed using the formula π = TR-TC to determine income and descriptive analysis to determine marketing mix strategy.